MESSAGE FROM THE DEAN - Nagi, Kuldeep (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2021)
Let me first congratulate and wish Merry Christmas and a very Happy New Year 2021 to all the authors and contributors to the new edition of eJIR. I am sure that every new opportunity in this new year will lead to a better life in 2021 and beyond. May the next edition of eJIR to be published in July 2021 bring more happiness, excitement, and sweet surprises to your doorstep!..... Download the file